Temporal shock wave analysis produced by copper exploding wires in air at atmospheric pressure - Barbaglia, Mario Oscar (2016)
In this work, experimental results concerning the temporal evolution of the shock wave radii generated by an exploding copper wire of fixed length are presented. The variables of the experience were the diameter dimension—from 50 to 500 μm—and the initial capacitor voltage—from 5 to 25 kV. The diagnostic device was a streak shadow image system synchronized with the experiment. The result is a parametric collection of data showing the shock wave position across the time depicting the different stages of the experience.